Biological Parameters, Environmental Effects, Dispersal Behaviour And Toxicological Studies Of The Tropical Bed Bug, Cimex Hemipterus (Fabricius) (Hemiptera: Cimicidae) - How , Yee Fatt (2010)
This thesis describes the biology, environmental effects, and dispersal behavior of the tropical bed bug, Cimex hemipterus (Fabricius), as well as the toxicological effects of eight insecticides (lambda-cyhalothrin, bifenthrin, fenitrothion, fipronil, imidacloprid, indoxacarb, chlorantraniliprole and DDT) on this species. The resurgence of bed bug infestations in recent years and infestation management also are discussed.